Development mode and practice of fault-block oriented shale oil well in the second member of Funing Formation, Qintong Sag, Subei Basin - YAO Hongsheng,YUN Lu,ZAN Ling,ZHANG Longsheng,QIU Weisheng (Youqicang pingjia yu kaifa)
In order to explore the beneficial development path of fault-block shale oil in Qintong Sag, a development mode for the fracturing of directional wells combined with pseudo-horizontal wells has been proposed based on the study on the geological characteristics of shale oil in the second member of Funing Formation, and two wells are successfully implemented. The results show that the east and west wings of the deep sag belt of Qitong Sag in Subei Basin are structural complex areas with fault-block shale reservoirs, which are with large thick, developed natural fracture network, high pressure coefficient, and good mobility and transformability. The geological conditions here is not suitable for the development of long horizontal wells but for the directional wells. For the multi-layer development of thick shale oil, the rectangular directional well pattern is conducive to the CO2 huff and puff, while the diamond reverse nine-spot well pattern is reasonable for the CO2 flooding. Therefore, with the fracturing technology system based on “large-scale liquid injection energy storage & flow limiting perforation promotion and equalization & flow adjustment and fracture-stabilizing network & three-stage support and maintenance filling & continuous construction with all electric pumps”, the fracturing of the directional wells took as the “pseudo-horizontal well” can achieve the transformation effect of the horizontal wells, and the transformation volume of the single stage is 28.6 % larger than that of horizontal wells. This new develop mode of shale oil has high initial productivity, early oil breakthrough time, low flowback rate, fast water cut decline, and long stable production time. The single stage has high elastic productivity, high recovery degree, and good economic benefits, realizing beneficial development of shale oil in advance. The beneficial development shows a good prospect for the evaluation of shale oil in complex structural areas by the directional wells.